A comprehensive embedded solution for data acquisition and communication using FPGA - Venkatraman Kandadai (Journal of Applied Research and Technology, 2017)
Digital controllers in real time applications require a reliable system for acquisition of data for effective processing. This paper focusses on the design and development of a comprehensive embedded solution for data acquisition and communication using field programmable gate array (FPGA). In the proposed solution, an embedded platform is developed which acquires the data, monitors and provides essential communication between the devices connected via Ethernet in a network. The system utilizes server/client architecture mode of communication; control signals for the appliances connected to the client are controlled by the server and the status of appliances are displayed at server end for online monitoring. The proposed embedded solution works without a dedicated personal computer. The versatility and efficacy of the proposed platform is tested experimentally by employing it in a prototype of laboratory built micro-grid.